Implementasi Sistem Informasi Manajemen Pendidikan di Madrasah Ibtidaiyyah Al-Mubarok Kecamatan Pinang Kota Tangerang - Tuzzzahro, Khilda (INTIFA: Journal of Education and Language, 2025)
This research explains the implementation of the Education management information system at MI Al Mubarok. The Education Management Information System was developed to meet the needs of madrasas or educational institutions where schools want to manage learning activities using computers as a contribution to madrasa or educational institution services and to simplify and speed up the teaching and learning process in schools and school services. This research uses a qualitative approach using observation, interviews and documentation as data collection techniques. The results of this research show that the implementation of the education management information system at MI Al Mubarok Pinang is realized in the form of using an application system including teaching and education staff services by activating the SIMPATIKA application (Information System for Educators and Education Personnel of the Ministry of Religion). School Instagram application and school website. There are several supporting and limiting factors in implementing SIMPATIKA at MI Al Mubarok, namely the availability of information system facilities and the existence of human resource obstacles and errors. ABSTRAK Penelitian ini menjelaskan tentang implementasi sistem informasi manajemen Pendidikan di MI Al Mubarok. Sistem Informasi Manajemen Pendidikan dikembangkan untuk memenuhi kebutuhan madrasah atau lembaga pendidikan dimana sekolah ingin mengelola kegiatan pembelajaran dengan menggunakan komputer sebagai kontribusi pelayanan madrasah atau lembaga pendidikan serta untuk mempermudah dan mempercepat proses belajar mengajar di sekolah dan layanan sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan observasi, wawancara, dan dokumentasi sebagai teknik pengumpulan data. Hasil penelitian ini menunjukkan bahwa implementasi sistem informasi manajemen pendidikan di MI Al Mubarok Pinang diwujudkan dalam bentuk penggunaan sistem aplikasi termasuk layanan pengajar dan tenaga kependidikan dengan mengaktifkan aplikasi SIMPATIKA (Sistem Informasi Pendidik dan Tenaga Kependidikan Kemenag). Aplikasi Instagram sekolahan dan web sekolah. Terdapat beberapa faktor pendukung dan pembatas dalam penerapan SIMPATIKA di MI Al Mubarok yaitu tersedianya fasilitas sistem informasi serta adanya kendala dan kesalahan sumber daya manusia.